Philippine dance an expression of life. ([Manila] ASEAN Cultural Exchange)
It shows the different dances of the Filipinos: tribal, Muslim, Spanish, folk, etc. and their origin and description.
VHS.
Keywords: Dancing -- Philippines; Human kinetics